(untitled) (The Research of Medical Science Review, 2025)
Background: Osteoporosis and diabetes mellitus represent significant challenges in global healthcare. Individuals diagnosed with type 2 diabetes mellitus (T2DM) exhibit a heightened susceptibility to osteoporosis. However, risk of osteoporosis and its clinical significance in our local diabetic population has rarely been investigated. Methodology: Study was carried out at Department of Medicine, Divisional Teaching Hospital, Mirpur, AJK. Total 185 patients of both genders having T2DM since last 12 months, having complaint of generalized body aches for at least one month and age between 18-80 years of both genders were enrolled for the study. Patients were labelled as positive for osteoporosis if BMD values showing T-score <-2.5. Entry and analysis of the data was carried out using SPSS software version 25.0. Results: Most of the study patients 118 (63.8%) were female. The mean age of participants was 43.39 ± 4.61 years, ranging from 24 to 50 years. The overall prevalence of osteoporosis in the study population was 24.3% (figure 1). A statistically significantly difference (p-value ≤ 0.05) was seen for uncontrolled and controlled diabetes, age groups and duration of diabetes. No statistically significant association was noticed for any of the other effect modifiers. Conclusion: Our study found 24.3% of type 2 diabetics had osteoporosis. Early screening and treatments in high-risk diabetics are crucial due to significant connections between osteoporosis and diabetic control, age, and duration. These findings underscore the importance of complete bone health treatment in diabetes therapy to prevent long-term skeletal problems.